Ideas of holistic engineering meet engineering work practices. Issue 2 (3rd May 2016) - Buch, Anders
ABSTRACT: This article critically reflects on the viability of the idea that reforming engineering education will result in more holistic engineering work practices. Drawing on an empirical study, the article aims to demonstrate that in order to change existing engineering work practices, it might be necessary to change engineers' knowledge and skills; however, such changes are far from sufficient. Conditions and circumstances external to practitioners' knowledge and skills are crucial if engineering work is to become more holistic. To illustrate this point, the article outlines an empirical study of a small team of professionals who engage in holistic engineering work practices in an engineering consultancy company. The work practices are investigated using a philosophical empirical method that inquires into the doings, sayings, and relatings of the practitioners. The study describes the practice architecture that shapes and is shaped by the practitioners' activities, and it demonstrate how the practice landscape prevents enactments of holistic engineering work practices.